2021
DOI: 10.1158/1535-7163.mct-20-0490
|View full text |Cite
|
Sign up to set email alerts
|

Anti-LYPD1/CD3 T-Cell-Dependent Bispecific Antibody for the Treatment of Ovarian Cancer

Abstract: Ovarian cancer is a diverse class of tumors with very few effective treatment options and suboptimal response rates in early clinical studies using immunotherapies. Here we describe LY6/PLAUR domain containing 1 (LYPD1) as a novel target for therapeutic antibodies for the treatment of ovarian cancer. LYPD1 is broadly expressed in both primary and metastatic ovarian cancer with ∼70% prevalence in the serous cancer subset. Bispecific antibodies targeting CD3 on T cells and a tumor antigen on cancer cells have de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Preclinical studies in mouse tumor models revealed a transient liver toxicity phenotype within 24 h following TDB treatment, which was resolved 4 days later. This phenotype included multiple necro‐inflammatory foci, variable perivascular, and periportal chronic inflammatory infiltrate, as well as focal early necrosis of hepatocytes surrounding the central vein, portal tracks, and within lobules (Lo et al , 2021 ). Furthermore, a single‐dose safety study in cynomolgus monkeys using TDB treatment revealed acute and transient off‐tumor activity, which is consistent with acute hepatocellular toxicity (Staflin et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies in mouse tumor models revealed a transient liver toxicity phenotype within 24 h following TDB treatment, which was resolved 4 days later. This phenotype included multiple necro‐inflammatory foci, variable perivascular, and periportal chronic inflammatory infiltrate, as well as focal early necrosis of hepatocytes surrounding the central vein, portal tracks, and within lobules (Lo et al , 2021 ). Furthermore, a single‐dose safety study in cynomolgus monkeys using TDB treatment revealed acute and transient off‐tumor activity, which is consistent with acute hepatocellular toxicity (Staflin et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…1B, C). Due to the relatively low recovery (7.9%) of malignant epithelial cells from the ascites of the 11 HGSOC patients, Izar et al analyzed an additional 1297 viable malignant cells isolated on the basis of EPCAM+/CD24+ flow sorting and sequenced by full-length scRNA-seq SMART-seq2 17 . In these data, PAX8, LYPD1, MUC16 and MSLN were expressed in most malignant epithelial cells (92, 87, 97, and 95%, respectively) and still expressed in a small population of fibroblasts also captured (23,3,84, and 83%, respectively) (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…LYPD1 is a GPI-anchored membrane protein with medium-to-high cell surface expression in HGSOC. The expression of LYPD1 is limited to tissues of origin, such as the fallopian tube and anterior pituitary gland, making it a compelling TCB target for HGSOC 17 .…”
Section: Introductionmentioning
confidence: 99%
“…T-BsAbs that target B7-H3, B7-H4, or B7-H6 have shown promising antitumor effects in mouse models against melanoma, breast cancer, and ovarian cancer, respectively [124][125][126]. Other distinctive target antigens include a lyase, a Wnt signaling regulator, an orphan receptor, and a sialylated cluster of differentiation (CD) antigen [57,[127][128][129]. Several T-BsAbs mentioned here are now in clinical trials for evaluation of their efficacy and safety.…”
Section: Preclinical Researchmentioning
confidence: 99%